ANALYSING LAW AND PROHIBITION IN DHARMASHASTRA: INSIGHTS FROM MANUSMRITI, YAJNAVALKYA SMRITI, AND PARASHARA SMRITI - 1. Dr. Subodhkant Mishra, 2. Sameer Harshad Pande (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
This research paper provides an in-depth examination of the principles of law (duty) and prohibition (restrictions) as articulated in the Dharmashastra, with a specific focus on Manusmriti, Yajnavalkya Smriti, and Parashara Smriti. It explores the foundational social and moral regulations prescribed within these ancient texts, analysing the duties and prohibitions applicable to the four varnas (Brahmin, Kshatriya, Vaishya, and Shudra) in Indian culture. The study underscores the significance of maintaining morality, discipline, and social harmony through the lenses of law and prohibition. It investigates the emphasis on ideals such as truth, non-violence, charity, and ritualistic sacrifices within the framework of laws, contrasting these with the social and spiritual consequences of prohibitions against adultery, violence, and unrighteousness. By referencing key ancient texts, this paper highlights the socio-ethical implications of these principles. Furthermore, the research emphasizes the contemporary relevance of these teachings, advocating for their reinterpretation to promote equality and moral integrity in modern society.